2016
DOI: 10.3389/fnhum.2016.00135
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Alternating Current Stimulation with Sawtooth Waves: Simultaneous Stimulation and EEG Recording

Abstract: Transcranial alternating current stimulation (tACS) has until now mostly been administered as an alternating sinusoidal wave. Despite modern tACS stimulators being able to deliver alternating current with any arbitrary shape there has been no systematic exploration into the relative benefits of different waveforms. As tACS is a relatively new technique there is a huge parameter space of unexplored possibilities which may prove superior or complimentary to the traditional sinusoidal waveform. Here, we begin to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…In a recent study, we applied tACS using various ‘sawtooth’ waves in addition to the traditional sinusoidal waveform (Dowsett & Herrmann, ); waveforms such as square waves and sawtooth waves, which contain sudden transitions in current, may be more effective at influencing or entraining neuronal oscillations, but they have an additional advantage in that the distinct properties of sawtooth waves, that is, consisting of straight lines with a steep transition, do not occur in nature and are more easily distinguishable from neural activity. This makes removing the artefact from the EEG recording simpler (see below).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we applied tACS using various ‘sawtooth’ waves in addition to the traditional sinusoidal waveform (Dowsett & Herrmann, ); waveforms such as square waves and sawtooth waves, which contain sudden transitions in current, may be more effective at influencing or entraining neuronal oscillations, but they have an additional advantage in that the distinct properties of sawtooth waves, that is, consisting of straight lines with a steep transition, do not occur in nature and are more easily distinguishable from neural activity. This makes removing the artefact from the EEG recording simpler (see below).…”
Section: Methodsmentioning
confidence: 99%
“…) unless (1) stimulation artifact removal depends on accurate field pick‐up (Helfrich et al . ; Dowsett and Herrmann ); (2) when recording hardware non‐linearities are of concern (Lesperance et al . ; Kasten et al .…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Amplifier and electrode attenuation may not be critical for conventional neurophysiological measures (e.g. action potential threshold or rate, low frequency oscillation power; Grossman et al 2017;Negahbani et al 2018) unless (1) stimulation artifact removal depends on accurate field pick-up (Helfrich et al 2014;Dowsett and Herrmann 2016); (2) when recording hardware non-linearities are of concern (Lesperance et al 2018; Kasten et al 2018); (3) when electrophysiological responses at kHz rate (e.g. kHz fluctuations in membrane potential) are of interest (Pelot et al 2017); and (4) when interactions between equipment and the body introduce complex distortions (Neuling et al 2017;Noury and Siegel, 2018;Gebodh et al 2019).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Transcranial stimulation is often used to enhance neural oscillations [25,26]. [27] showed that transcranial 276 alternating current stimulation (tACS) with sawtooth waves is more effective at enhancing alpha-frequency 277 oscillations than tACS with sinusoidal waves; whether tACS predominantly excites interneurons or principal cells 278 depends on the intensity of stimulation [28]. Our work suggests that, given an excitatory intensity, tACS 279 stimulation with square waves (i.e., periodic pulses) could be even more effective at enhancing neural oscillations.…”
mentioning
confidence: 99%